Summertime M2 Internal Tides in the Northern Yellow Sea - Lin, Fan; Asplin, Lars; Wei, Hao (Frontiers in Marine Science, 2021)
The summertime M2 internal tide in the northern Yellow Sea is investigated with moored current meter observations and numerical current model results. The hydrodynamic model, which is implemented from the Regional Ocean Model System (ROMS) with 1 km horizontal resolution, is capable of resolving the internal tidal dynamics and the results are validated in a comparison with observations. The vertical pattern of a mode-1, semi-diurnal internal tide is clearly captured by the moored ADCP as well as in the simulation results. Spectral analysis of the current results shows that the M2 internal tide is dominant in the northern Yellow Sea. Analysis of the major M2 internal tide energetics demonstrated a complex spatial pattern. The tidal mixing front along the Korean coast and on the northern shelf provided proper conditions for the generation and propagation of the internal tides. Near the Changshan islands, the M2 internal tide is mainly generated near the local topography anomalies with relatively strong current magnitude, equal to about 30% of the barotropic component, thus modifying the local current field. These local internal tides are short-lived phenomena rapidly being dissipated along the propagation pathway, restricting their influence within a few kilometers around the islands.